Optimization formulation of chamomile-based functional beverage as hypnotic agent using response surface method - Annisa Ulfah Pristya; Tri Dewanti Widyaningsih (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Insomnia problem can be treated by consuming herbs containing apigenin and EGCG. Chamomile and green tea water extract have been found to containapigenin and EGCG. Optimization of the formulation of those herbs is necessary to obtain the highest hypnotic activity. The purpose of this study was to optimize formulation of chamomile, green tea, and cinnamon to obtain functional beverage containing the highest phenolic and flavonoid content, but the lowest caffeine content. The best formula of the herbs was then tested in caffeine-induced mice to see the hypnotic effect. The research design in this experiment was Response Surface Model (RSM) using Central Composite Design (CCD) method. The in vivo test used Post Test Only Control Group Design. Consisting five groups of 30 male mice divided to 6 mice for each group. The optimum formula for functional beverages suggested by RSM was chamomile: green tea : cinnamon of 70.32 : 30.35 : 4.99. The verification results showed that the actual response of this optimum formula had a total phenol of 23.76 mgGAE/g dry herbs, total flavonoids of 126.43 mgQE/g dry herbs, caffeine content of 29.87 mg caffeine/g dry herbs, apigenin levels of 0.07±0.068 µg/g dry herbs, and EGCG of 6.43±0.218 µg/g dry herbs. Functional beverages showed hypnotic activity in group of mice dosed 26 mL/kg bw, which significantly reduced motor activity to 4.83±0.72 sec. As well as significantly reducing the proinflammatory cytokines